The provisional nature of science evidenced in times of pandemic (Alternautas, 2022)
Trust in science has been problematic over the years. The roots of the problem, in turn, are deep. For a long time, it was believed that the primary obstacle would center on the need for greater provision of scientific information to the non-specialist audience. However, this is a deficit view of the public “understanding” of science and technology, which disregards the associated historical, social and political contexts. The Digital Age has made this issue even more evident, as scientific information is everyday more rapidly accessible online. During the Covid-19 pandemic, global efforts mobilized to share information about this unprecedented scenario, bringing science to the spotlight. Consequently, the population followed every new discovery on-demand, from public policy to vaccine development challenges. This panorama puts the science trust in check again: social media gave voice not only to scientists, but also to any user to express their frustrations on this provisional moment, highlighting what was already known by academics: knowledge is constantly changing.